Online Learning Strategies For Indonesian Language Teachers In Improving Student Learning Effectiveness In Class VII SMP Negeri Lhokseumawe - Juni Ahyar; T Edyansyah; Ikramuddin Ikramuddin (CV. Green Publisher Indonesia, 2021)
Background: Because of the Covid-19 pandemic, there appears to be a major shift in learning processes at all levels of education. Online learning is a teaching activity carried out through virtual videos without face to face and using internet technology. The importance of the teacher's method in the online learning process cannot be isolated from the emergence of numerous hurdles experienced by students in this study. Particularly in Indonesian language subject, where these subjects are already well-known for containing a great deal of theory and narrative. Teachers must utilize proper tactics when teaching, especially in Indonesian subject, to make the teaching and learning process effective and not boring. Research purposes: This research aims to the most popular Indonesian language tactics employed in the online learning process in Indonesia, to describe how the teacher has implemented Indonesian tactics to improve the effectiveness of the online learning process in Indonesian class VII subjects in junior high school, and to discuss the Indonesian language barriers that teachers experience while teaching online. Research methods: A qualitative research approach was employed with the type of case study research to attain the desired aims. The Indonesian class teacher was a crucial component. Interviews, observation, and documentation were utilized to obtain data. By removing extraneous data, presenting data, and drawing conclusions, the data was evaluated. Research result: The learning system has shifted from face to face to online, then gave rise to various responses and obstacles as well as changes in learning models in Indonesia, including teachers who directly deal with students. Several teachers and students experience problems when carrying out online learning including New and unfamiliar learning applications, limited internet data, learning management, assessment, and supervision that is not optimal. Conclusion: The learning method is also adapted to this online period so that learning activities remain effective even though behind it there are many shortcomings. From the whole method, the researchers conclude that the method that is mostly used by the teacher council is by providing learning materials through Whatsapp groups, using Google Classroom, and for students who do not understand or are less capable in the field of technology, they can come directly to the school. This is also enforced so that students continue to receive materials during the school period. In addition, the teachers give tolerance to every student who is late in collecting assignments because during the pandemic there are certainly many obstacles experienced by students.